Blending Non‐Group‐3 Transition Metal and Rare‐Earth Metal into a C80 Fullerene Cage with D5h Symmetry. (7th March 2018) - Wei, Tao; Jin, Fei; Guan, Runnan; Huang, Jing; Chen, Muqing; Li, Qunxiang; Yang, Shangfeng
Abstract: Rare‐earth metals have been mostly entrapped into fullerene cages to form endohedral clusterfullerenes, whereas non‐Group‐3 transition metals that can form clusterfullerenes are limited to titanium (Ti) and vanadium (V), and both are exclusively entrapped within an Ih ‐C80 cage. Non‐Group‐3 transition‐metal‐containing endohedral fullerenes based on a C80 cage with D 5 h symmetry, V x Sc3− x N@ D 5 h ‐C80 ( x= 1, 2), have now been synthesized, which exhibit two variable cluster compositions. The molecular structure of VSc2 N@ D 5 h ‐C80 was unambiguously determined by X‐ray crystallography. According to a comparative study with the reported Ti‐ and V‐containing clusterfullerenes based on a Ih ‐C80 cage and the analogous D 5 h ‐C80 ‐based metal nitride clusterfullerenes containing rare‐earth metals only, the decisive role of the non‐Group‐3 transition metal on the formation of the corresponding D 5 h ‐C80 ‐based clusterfullerenes is unraveled.